1998
DOI: 10.1046/j.1365-2788.1998.00134.x
|View full text |Cite
|
Sign up to set email alerts
|

A community survey of children with severe intellectual disability and their families: psychological adjustment, carer distress and the effect of respite care

Abstract: The present paper describes a cross-sectional study of the psychosocial adjustment of 143 children with severe disability and their families identified from a regional case register for children with special needs. Thirty-eight per cent of the children had significant psychiatric morbidity. By contrast, the overall level of distress in carers was not that different from probable community prevalence figures. Nevertheless, distress among carers was consistently associated with increased disability in the child.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
91
2
6

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(106 citation statements)
references
References 10 publications
7
91
2
6
Order By: Relevance
“…Socio-economic status were reported not to be related to parental depression in families with children with intellectual disability (26,35). In our study employed mothers had significantly higher state anxiety, trait anxiety, and depression scores in the autism group whereas occupation showed no significance in the mental retardation group.…”
Section: Discussioncontrasting
confidence: 65%
“…Socio-economic status were reported not to be related to parental depression in families with children with intellectual disability (26,35). In our study employed mothers had significantly higher state anxiety, trait anxiety, and depression scores in the autism group whereas occupation showed no significance in the mental retardation group.…”
Section: Discussioncontrasting
confidence: 65%
“…reported that the availability of support from friends and family facilitated positive perceptions, since families felt that they had external resources they could depend on to cope with their situation. and other researchers (Hoare et al, 1998;Horton & Wallander, 2001;Plant & Saunders, 2007) found that those families with more social support showed lower levels of distress than those with less social support.…”
Section: A Pattern Of Communication That Emphasises and Encourages Opmentioning
confidence: 81%
“…Psychological help is received mostly due to the effects of the mental disability on the parents. Previous researches proved that parents that have a disabled child undergo social suppression and experience hopelessness, future worries and higher depression and feel regret more intensely (Hoare et al 1998). Therefore, we may say that children of the parents that received psychological help had lower self concept.…”
Section: Discussionmentioning
confidence: 99%